Hubungan motivasi dan beban kerja dengan kinerja perawat pelaksana di rumah sakit - Siregar, Sakti Perdana; Nurhidayah, Rika Endah; Siregar , Farida Linda Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Nurse performance is crucial in determining the quality of nursing care in hospitals. Low motivation and high workload are factors contributing to decreased performance. This occurs at Rasyida Kidney Specialist Hospital, Medan, characterized by a lack of appreciation, high workload, and patient complaints regarding services. Purpose: To analyze the relationship between motivation and workload and nurse performance. Method: This study used a correlational analytical design with a cross-sectional approach. The study population was all nurses at Rasyida Kidney Specialist Hospital, Medan. The sample size was 69. The research instrument was developed by the researcher and has undergone validity and reliability testing. Data analysis was conducted using univariate, bivariate, and multivariate methods. Results: Univariate analysis showed that the majority of nurses (45%, 65.2%) had good motivation, 48 (69.6%) had a high workload, and 46 (66.7%) had adequate performance. The analysis of the relationship between motivation and performance yielded a p-value of 0.001 and an r-value of 0.507, while the analysis of the relationship between workload and nurse performance yielded a p-value of 0.012 and an r-value of 0.301. Conclusion: There is a relationship between motivation, workload, and nurse performance, with a coefficient of determination of R2 = 0.357, indicating a 35.7% effect of the independent variable on the dependent variable. Suggestion: This finding is expected to serve as a basis for evaluating hospital policies related to nurse motivation and workload. Strategies are needed to create a workload balance to support sustainable nurse performance. Keywords: Hospital; Motivation; Nurses; Performance; Workload. Pendahuluan: Kinerja perawat penting dalam menentukan kualitas pelayanan keperawatan di rumah sakit. Rendahnya motivasi dan tingginya beban kerja menjadi faktor penurunan kinerja. Ini terjadi di Rumah Sakit Khusus Ginjal Rasyida Medan, ditandai kurangnya penghargaan, tingkat kerja tinggi, adanya keluhan pasien terhadap pelayanan. Tujuan: Untuk menganalisis hubungan motivasi dan beban kerja dengan kinerja perawat pelaksana di rumah sakit. Metode: Penelitian menggunakan desain analitik korelasional dengan pendekatan cross sectional. Populasi penelitian adalah seluruh perawat pelaksana di Rumah Sakit Khusus Ginjal Rasyida Medan. Sampel merupakan populasi (total sampling) berjumlah 69. Instrumen penelitian dikembangkan sendiri oleh peneliti dan telah dilakukan uji validitas dan reliabilitas. Analisis data dilakukan secara univariat, bivariat, dan multivariat. Hasil: Mayoritas motivasi cukup baik 45 (65.2%), beban kerja tinggi 48 (69.6%), dan kinerja perawat cukup 46 (66.7%). Hasil analisis hubungan motivasi dengan kinerja didapatkan p-value 0.001 dan nilai r 0.507, sedangkan hasil analisis hubungan beban kerja dengan kinerja perawat didapatkan p-value 0.012 dan nilai r 0.301. Simpulan: Terdapat hubungan antara motivasi dan beban kerja dengan kinerja perawat pelaksana dengan koefisien determinasi R2= 0.357 yang berarti besarnya pengaruh variabel independen terhadap variabel dependen adalah sebesar 35.7%. Saran: Diharapkan menjadi dasar evaluasi kebijakan rumah sakit terkait motivasi dan beban kerja perawat, diperlukan strategi untuk menciptakan keseimbangan beban kerja guna mendukung kinerja perawat secara berkelanjutan. Kata Kunci: Beban Kerja; Kinerja; Motivasi; Perawat; Rumah Sakit.